COVID-19 vaccination, herd immunity and the transition toward normalcy: Challenges with the upcoming sports event - Dergaa, I.; Abdelrahman, H.; Varma, A.; Yousfi, N.; Souissi, A.; Ghram, A.; Hammad, A. S.; Musa, E. R.; Taheri, M.; Irandoust, K.; Chtourou, H.; Rafiei, M. M.; et al. (Annals of Applied Sport Science, 2021)
Background. The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has created an unprecedented and daunting challenge for humanity to survive. This has also affected the sporting events across the globe as the majority of the tournaments have been cancelled or postponed as a result. For life to return to pre-pandemic normalcy, an effective and safe vaccination program needs to be implemented, be readily accessible, widely available, and affordable at the same time. Objectives. In this review, we analyze various challenges which demonstrate that COVID-19 is far from over. Methods. A systematic literature search was conducted on PubMed, ScienceDirect, Medline, Google Scholar, and Scopus from the commencement of the COVID-19 pandemic to 22 June 2021. The current report is a summary of data regarding challenges faced by the COVID-19 vaccination campaign and the challenges for a transition toward normalcy, especially for big sports events. Results. The current COVID-19 pandemic has likely resulted in sporting events and tournaments being canceled, postponed, or held without or with restricted spectators around the world. A combination of measures including prompt vaccination with the beneficial impact of the vaccines in reducing the severity of disease, advances in treatment, expanded use of diagnostics and better implementation of public-health policies are a necessity. Following this implementation, a transition toward normality could be expected when the mortality rate of COVID-19 simulates the average influenza statistics, with public-health measures continuing to play an important role worldwide. Conclusion. The authors believe that COVID-19 will be endemic in the human population, similar to seasonal influenza and that COVID-19 vaccines will be included as an add-on to seasonal influenza vaccinations, being administered every winter for at least the next few decades. With adequate vaccination, the sporting world will be able to withstand the challenges and resume global events, returning to pre-Covid levels of normalcy.